Separation of Powers, Political Competition and Efficient Provision of Public Goods - Aristotelis Boukouras; Kostas Koufopoulos (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
In this paper we provide a political game where agents decide whether to become legislators or politicians. Legislators determine the political institutions constraining politiciansb́ehavior and politicians compete for gaining the power to make decisions about the level of the public good. We derive the following results: i) Political competition is a necessary but not a suffcient condition for the elimination of political rents. ii) Agents utilize the separation of powers in order to endogenously select institutions which restrict the power of politicians. iii) In conjunction with political competition, these institutions implement the Lindahl allocation in the economy as a sub-game perfect Nash equilibrium of the political game. iv) As a consequence of the previous result, political rents are zero in equilibrium, in the sense that the winning politician does not extract part of the social surplus because of his power. To the best of our knowledge, this in the only citizen-candidate model with this equilibrium property.
Keywords: D02; D62; D72; H41; 330; Lindahl allocation; political competition; voting games